2021
DOI: 10.1038/s41467-021-26046-9
|View full text |Cite
|
Sign up to set email alerts
|

Protein identification by nanopore peptide profiling

Abstract: Nanopores are single-molecule sensors used in nucleic acid analysis, whereas their applicability towards full protein identification has yet to be demonstrated. Here, we show that an engineered Fragaceatoxin C nanopore is capable of identifying individual proteins by measuring peptide spectra that are produced from hydrolyzed proteins. Using model proteins, we show that the spectra resulting from nanopore experiments and mass spectrometry share similar profiles, hence allowing protein fingerprinting. The inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 53 publications
2
85
0
Order By: Relevance
“… 18 Single proteins are then addressed by directly reading the unfolded protein as it translocated across the nanopore or by chopping the protein into peptides and reading the fragments in sequence. 19 We also showed that the latter “chop and drop” method could potentially discriminate among the majority of proteins of the human proteome, provided that most peptides were accurately detected by the nanopore. 20 α-Helical fragaceatoxin C (FraC) nanopores were shown to efficiently capture peptides in low pH conditions regardless of their charge.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“… 18 Single proteins are then addressed by directly reading the unfolded protein as it translocated across the nanopore or by chopping the protein into peptides and reading the fragments in sequence. 19 We also showed that the latter “chop and drop” method could potentially discriminate among the majority of proteins of the human proteome, provided that most peptides were accurately detected by the nanopore. 20 α-Helical fragaceatoxin C (FraC) nanopores were shown to efficiently capture peptides in low pH conditions regardless of their charge.…”
mentioning
confidence: 73%
“… 20 α-Helical fragaceatoxin C (FraC) nanopores were shown to efficiently capture peptides in low pH conditions regardless of their charge. 19 , 21 23 In turn, this allowed several proteins to be recognized by measuring the peptide spectrum originating from trypsinated proteins. Although this approach is capable of distinguishing among proteins at the single-molecule level, it is unclear whether a cylindrical β-barrel nanopore, such as those incorporated into the nanopore–unfoldase complex, can be engineered to identify proteinogenic peptides in a fashion similar to conical α-helical FraC nanopores.…”
mentioning
confidence: 99%
“…One method is to adopt a protein fingerprinting approach like the shotgun proteomics used in mass spectrometry. 8 The other strategy employs DNA motor enzymes to ratchet a peptide–oligonucleotide conjugate into the nanopore. 6,7,9 The former method requires the digestion of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Ion currents have been widely used to monitor various biosamples, such as cells [13], bacteria, viruses, peptides [14], and DNAs [15,16] passing through nano/micropores. In addition to nanopores based on biomaterials [17], solid-state nanopores have also been employed [18].…”
Section: Introductionmentioning
confidence: 99%